"Real Owners" and "Common Investors": Institutional Logics and the Media as a Governance Mechanism. (31st August 2012) - Jansson, Andreas
Abstract: Manuscript Type: Empirical Research Question/Issue: Based on an analysis of Swedish press material covering two corporate scandals, this paper reveals the institutional logic propagated by the Swedish press pertaining to large shareholders and the relationship between this institutional logic and the attribution of blame for the scandals to shareholders by the press. Research Findings/Insights: The results reveal an institutional logic with a clear notion of what constitutes a "real owner, " which is reminiscent of an understanding of ownership and control prevalent in the literature before the emergence of agency theory. Real owners are associated with moderation of management, responsibility, long‐termism, and legitimate influence in the firm. In response to scandals, this institutional logic leads the Swedish press to question the "realness" of an existing controlling shareholder or, if no controlling shareholder exists, to blame the problem on the absence of a real owner. Theoretical/Academic Implications: It is important to understand the institutional logic propagated by the press to see how the media functions as a governance mechanism, since a given institutional logic leads the media to "name and shame" in specific ways. The institutional logic propagated by the Swedish press differs from what previous research has indicated is prevalent in the US, suggesting that the media as a governance mechanism has different effects in different countries. Practitioner/Policy Implications: This paper illustrates the importance of understanding prevalent informal norms when predicting effects of corporate governance reform and suggests that these informal aspects are highly path dependent.